Protective effect of ellagic acid on oxidative stress and antioxidant status in Cyprinus carpio during malathion exposure - Ural, M. S.; Yonar, M. E.; Yonar, S. Mise (C M B Assoc, 2015)
This study aims to determine protective efficiency of ellagic acid (EA) on malathion toxicity in carp. The fish were exposed to two sublethal concentrations of malathion (0.5 and 1 mg/L), and EA (100 mg per kg of fish weight) was simultaneously administered for 14 days. Malondialdehyde (MDA) level and superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and glutathione-S-transferase (GST) activities were evaluated in liver, kidney and gills, which were collected at the end of the experiment. In conclusion, the findings of this study demonstrated that malathion caused oxidative stress and negative alterations on the antioxidant enzyme activities of the fish. However, this toxic effect was neutralised by the administration of EA. Thus, the present results suggest that simultaneous treatment with EA (100 mg per kg of fish weight) may alleviate malathion-induced oxidative stress.
Keywords: Malathion; Ellagic acid; Oxidative stress; Antioxidant enzyme; Carp